2022
DOI: 10.1021/acs.est.2c03333
|View full text |Cite
|
Sign up to set email alerts
|

Review and Prospects on the Ecotoxicity of Mixtures of Nanoparticles and Hybrid Nanomaterials

Abstract: The rapid development of nanomaterials (NMs) and the emergence of new multicomponent NMs will inevitably lead to simultaneous exposure of organisms to multiple engineered nanoparticles (ENPs) at varying exposure levels. Understanding the joint impacts of multiple ENPs and predicting the toxicity of mixtures of ENPs are therefore evidently of importance. We reviewed the toxicity of mixtures of ENPs to a variety of different species, covering algae, bacteria, daphnia, fish, fungi, insects, and plants. Most studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…To sum up, the joint effects of DCA and TDNMs on the freshwater algae are mainly additive, antagonistic, and synergistic, which are related to the type of species and the concentration of the mixed components. Previous studies also show joint toxic action with different types in the same mixture of ENPs and co-existing contaminants depending on test species [ 4 ] and the exposure levels of test materials [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, the joint effects of DCA and TDNMs on the freshwater algae are mainly additive, antagonistic, and synergistic, which are related to the type of species and the concentration of the mixed components. Previous studies also show joint toxic action with different types in the same mixture of ENPs and co-existing contaminants depending on test species [ 4 ] and the exposure levels of test materials [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reality of pollution in the natural or artificial environment is that it is mostly a combined pollution. This also means that ENPs rarely exist alone but enter the environment at the same time as, or in sequence with, other pollutants and interact with each other to form combined pollution [ 4 ]. It is undeniable that the combined effect of ENPs with other pollutants on organisms is a worthwhile concern.…”
Section: Introductionmentioning
confidence: 99%
“…Size and surface potential affect the biological safety, distribution and transport process of nanomaterials. Studies have shown that the toxicity of nanomaterials increases with the decrease of particle size (< 100 nm), while oversized particles (> 10 μm) have the risk of microvascular embolism [ 46 48 ]. HE staining results showed no obvious histopathological changes in the main organs of the mice (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, the projected increased use and inevitable environmental release of various MNPs will result in ecosystems being subject to a wide range of mixtures of MNPs in varying compositions and varying concentrations. , Therefore, this study contributes important insights to better understand the bioaccumulation of MNPs via the food chain and the associated environmental risks under a more realistic exposure scenario. Our findings showed large variations in the MNPs’ transfer from plants to consumers.…”
Section: Discussionmentioning
confidence: 99%